A new anti-tumor cytotoxic triterpene from Ganoderma lucidum. Issue 16 (29th July 2022) - Cao, Liping; Jin, Hongliu; Liang, Qi; Yang, Haiyi; Li, Shuguang; Liu, Zhicheng; Yuan, Zhongwen
Abstract: Ganoderma lucidum ( G. lucidum ) is a famous medicinal fungus used as a traditional medicine for generations in China. Among bioactivities that G. lucidum possesses, the anti-tumor effect has aroused extensive interests. In this study, one new triterpene (1 ) was isolated from 90% ethanol extract of the dried fruiting bodies of G. lucidum . Its structure was determined based on the analysis of its spectroscopic data, including 1 D and 2 D NMR and MS spectra. Furthermore, 1 elicited moderate anti-tumor activities (IC50 values of 15.38 ± 0.34 and 18.61 ± 0.55 μM for A549 and HepG2 cells, respectively) compared with cisplatin which was employed as the positive drug with IC50 values of 8.21 ± 0.17 and 5.36 ± 0.29 μM for A549 and HepG2 cells, respectively. The mechanism study by RT-qPCR and western blot analysis suggested that the p53/caspase-3 pathway is involved in the 1 -induced apoptosis. Graphical Abstract: UF0001